Pozasądowe formy reakcji na zachowania dewiacyjne dzieci i młodzieży w Anglii i Walii - Muskała, Maciej (Wydawnictwo Naukowe UAM, 2012)
Antisocial behaviors are displayed more often by children and young people nowadays. This situation must lead to modification of current proceedings. One tire may be seen in prevention and early intervention undertaken not by the criminal justice system but the local authorities. Giving the example of England and Wales system, the author puts forward the whole range of diversion which may be applied in case of juvenile violating the normative order.
Keywords: zachowania dewiacyjne; nieletni; pozasądowe formy reakcji; Youth Offending Teams